Consistent View-Based Management of Variability in Space and Time - Ananieva, Sofia (The Karlsruhe Series on Software Design and Quality, 2022)
Developing variable systems faces many challenges. Dependencies between interrelated artifacts within a product variant, such as code or diagrams, across product variants and across their revisions quickly lead to inconsistencies during evolution. This work provides a unification of common concepts and operations for variability management, identifies variability-related inconsistencies and presents an approach for view-based consistency preservation of variable systems.